WELLBEING: A PHOTOVOICE EXPLORATION OF HEALTH AMONG OLDER ADULTS EXPERIENCING HOMELESSNESS. (11th November 2018) - Souza, A; Henthorn, L; Martin, F; Bowery, R; Howard, C
Abstract: Nationwide older adults experiencing homelessness is on the rise. Of the 554, 000 homeless individuals in the United States, half are over the age of 50. People experiencing homelessness face a variety of barriers in attaining and maintaining physical and mental health. These barriers are often insurmountable for older adults. The purpose of this investigation was to explore the facilitators and barriers to wellbeing in a sample of male adults over age 50 who are homeless and utilizing a night shelter in Seattle. We used an interpretive phenomenological approach with a photovoice methodology. Disposable cameras were distributed and participants were trained in their use. Participants photographed facilitators and barriers to their wellbeing during a one week data collection period. The study sample includes 5 men ranging in age from 51–72, with an average duration of homelessness of 2–24 months. All participants resided in Seattle prior to becoming homeless. Two semi-structured focus groups were held to discuss the meanings captured by their photographs. The meeting was audio recorded, transcribed verbatim, and themes were extracted utilizing Dedoose software. Study results showed that older adults have unique unmet needs, such as a lack of established services tailored to this population. Positive themes were also identified, such as resilience, community support, and insight into health promotion strategies. Information gained from this project can serve as a tool to inform policy change towards efficacious person-centered solutions for older adults experiencing homelessness.